Perancangan Model Real Time – Shop Floor Control System untuk Flexible Manufacturing System - Setiawan, Ari; Elroy, Mikha (Jurnal Telematika, 2020)
The ITHB Industrial Engineering Study Program plans to create a Flexible Manufacturing System (FMS) model for the learning process. FMS is a manufacturing system consisting of a workstation, material handling system, storage, or Automatic Storage and Retrieval System (AS / RS), and a computer management system. The workstations in the system studied consist of four CNC machines and two loading/unloading stations for loading and unloading workpieces and attaching workpieces to a fixture. The FMS has a computer control system that makes the system on the model under study run automatically. The monitoring system in the FMS model is a Shop Floor Control System (SFCS) which provides real-time information on the status of the workpiece, part number, number, operation, tool type requirements, and location of the workpiece. One method to build a Shop Floor Control System model is to use Object-Oriented Modeling (OOM). OOM describes the state (state), nature (behavior), and identity (identity) for each workpiece. In this research, an SFCS model has been designed and developed using integrated hardware, software, and interfaces. The hardware consists of a microcontroller and an RFID reader which is used to retrieve data. Software is used to process, send, and store data into a database. The interface serves as an interface to show these data and confirm the movement of the workpiece. The model developed has been tested with several kinds of data and status conditions, as well as the location of the workpiece. From the monitoring results, the SCFS model can show the accuracy of the status and location of the workpiece in real-time.Program Studi Teknik Industri ITHB berencana membuat model Flexible Manufacturing System (FMS) untuk proses pembelajarannya. FMS merupakan sistem manufaktur yang terdiri atas stasiun kerja, sistem penanganan material, penyimpanan, atau Automatic Storage and Retrieval System (AS/RS), dan sistem pengaturan komputer. Stasiun kerja dalam sistem yang dikaji terdiri atas empat mesin CNC dan dua loading/unloading station untuk membongkar muat benda kerja serta memasang benda kerja pada sebuah fixture. FMS memiliki sistem pengaturan komputer yang membuat sistem pada model yang dikaji bekerja secara otomatis. Sistem pengawasan pada model FMS merupakan Shop Floor Control System (SFCS) yang memberikan informasi mengenai status benda kerja, part number, jumlah, operasi, kebutuhan jenis pahat, dan lokasi benda kerja secara real-time. Salah satu metode untuk membangun model Shop Floor Control System adalah dengan menggunakan Object Oriented Modelling (OOM). OOM menjelaskan keadaan (state), sifat (behavior), dan identitas (identity) untuk setiap benda kerja. Pada penelitian ini telah dirancang dan dikembangkan sebuah model SFCS menggunakan hardware, software, dan interface yang saling terintegrasi. Hardware terdiri dari microcontroller dan RFID reader yang digunakan untuk mengambil data. Software digunakan untuk mengolah, mengirim, dan menyimpan data ke dalam database. Interface berfungsi sebagai antarmuka untuk menunjukkan data-data tersebut dan mengonfirmasi terjadinya perpindahan benda kerja. Model yang dikembangkan telah diuji coba dengan berberapa macam data dan kondisi status, serta lokasi benda kerja. Dari hasil monitoring, model SCFS dapat menunjukkan ketepatan status dan lokasi benda kerja secara real-time.